The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d3cy00071k
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-modulated binding selectivity of reaction substrates to onium-based σ-hole donors

Abstract: The combination of experimental data and results of DFT calculations indicates that the catalytic activity of chalconium and halonium salts serving as sigma-hole donating organocatalysts cannot be clearly estimated via...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…The reversible amine-aldehyde coupling giving a Schiff base (Figure 4) was carried out in the presence of any of Cat1 OTf - Cat4 OTf (10 mol %) or AgOTf (10 mol %), or the mixture of any of Cat1 OTf -Cat4 OTf and AgOTf (1 : 1, total 20 mol % of the electrophiles). The kinetic data, obtained by us using the same kinetic equations as in our previous work on Schiff condensation, [21] indicate that this reaction is catalyzed either by the silver(I) triflate or the iodonium triflates (Table 1, entries 1, 2, 3, 5, 7, 9). A rough approximation of the expected reaction rate constants for separate catalysis of the reaction by the mixture of silver(I) and iodine(III) centers [k f (AgOTf…”
Section: Electrophilic Activation Of the Carbonyl Group In Schiff Con...mentioning
confidence: 60%
“…The reversible amine-aldehyde coupling giving a Schiff base (Figure 4) was carried out in the presence of any of Cat1 OTf - Cat4 OTf (10 mol %) or AgOTf (10 mol %), or the mixture of any of Cat1 OTf -Cat4 OTf and AgOTf (1 : 1, total 20 mol % of the electrophiles). The kinetic data, obtained by us using the same kinetic equations as in our previous work on Schiff condensation, [21] indicate that this reaction is catalyzed either by the silver(I) triflate or the iodonium triflates (Table 1, entries 1, 2, 3, 5, 7, 9). A rough approximation of the expected reaction rate constants for separate catalysis of the reaction by the mixture of silver(I) and iodine(III) centers [k f (AgOTf…”
Section: Electrophilic Activation Of the Carbonyl Group In Schiff Con...mentioning
confidence: 60%
“…The nucleophilic species accumulating during the reaction progress can occupy the catalyst's σ-holes and, thus, effectively compete with the starting species for the coordination to the catalyst. 35 This can explain the high initial reaction rate, leading to approximately 5% conversion of the starting imine A within the first 4 min of the reaction (Figure 3) followed by a notable decrease of the reaction rate. This suggestion is indirectly confirmed by the presence of such a conversion leap in the case of σ-holedonating 1(BH 3 CN)−6(BH 3 CN) reagents and its absence in the case of utilization of Na(BH 3 CN) and n Bu 4 N(BH 3 CN), as well as by the retention of this leap in the case of reaction carried out in the presence of 2,6-di-tert-butylpyridine (10 mol %), which would neutralize traces of a Brønsted acid if they were present in 1(BH 3 CN)−6(BH 3 CN) as an impurity and catalyze the reaction at the beginning of its progress (see Figure S2 for the sulfonium cyanoborohydride).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For XB donors, it has been demonstrated that iodoazoliums 11−15 and iodopyridiniums 16 featuring an exocy-clic iodine(I) center effectively catalyze an extensive series of organic transformations, whereas hypervalent iodine(III) species (iodonium salts) possess even a greater catalytic activity than the iodine(I) derivatives. 17−23 For ChB donors, recent publications unambiguously indicate that telluronium salts (R 3 Ch + X − , Ch = Te IV ) exhibit a significantly higher Lewis acidity compared to the tellurium(II) derivatives and lighter chalcogen(IV)-derived species, 24−32 whereas selenonium salts (Ch = Se IV ) have a higher 33,34 or comparable 35 activity than their sulfonium analogues (Ch = S IV ), which, in turn, exhibit a sufficient catalytic activity toward a series of model organic transformations. 34,36 Although some of the σ-hole carriers 36−43 �similarly with well-studied HB donors 44 �were tested in the reaction of hydrogenation of the imine moiety by the Hantzsch esters (Scheme 1), 45 no examples were known for their applications involving simple inorganic reducing agents, such as hydrides, which might be explained by possible redox side reactions between the cationic σ-hole carrier and the reducing agent.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the pre-association processes involving the catalyst was not considered in the calculations despite its important role in catalysis, as recently demonstrated by the same authors. [62] Nevertheless, this study emphasized the role of side-interactions in chalconiums and pnictoniums which cooperate with the σ-hole interaction for the stabilization of the reactions transition states (Scheme 13).…”
Section: Telluronium Catalystsmentioning
confidence: 93%